Learning Diagnostic Imaging 100 Essential Cases - Ribes, Ramón; Luna, Antonio; Ros, Pablo R. (Learning Imaging, 2008)
In my ? rst days as a Radiology resident I remember myself in dire need of a book in which I could begin to study the specialty. In those days I was thirsty for radiolo- cal knowledge and was recommended a classic manual on conventional chest X-ray which was the very same the oldest radiologist of the staff had studied when he was a beginner. Unfortunately the book I was recommended covered less than 5% of the specialty as it is conceived nowadays. "Learning Diagnostic Imaging. A Teaching File" is intended to provide medical students, residents of Radiology, and anybody else beginning to be involved in the radiological world, with a useful tool that gives them a quick and comprehensive overview of Radiology. With this book, written in a user-friendly format, Radiology residents, nurses, technicians, and medical students would see their ? rst radiolo- cal images in a sort of introduction of what will become their professional activities in the rest of their lives.